Assessment of Anxiety and Depression Among Patients with COPD (Academia Journal of Medicine, 2021)
Background: The aim is to assess anxiety and depression among patients with COPD. Subjects and Methods : One hundred five adult patients in age ranged 20-60 years of either sex diagnosed with COPD were included. Parameters such as name age, smoking habit, history of alcoholism, duration of treatment, type of family, education and occupation etc. was recorded. The level of anxiety and depression among patients was recorded. Results: Out of 105 patients of COPD, males constituted 45 (39.2%) and females 65 (61.8%). The level of anxiety was low in 68, moderate in 25 and severe in 12. Depression was found to be normal in 23, mild in 30, borderline in 11, moderate in 25, severe in 6 and extreme in 5 patients. A significant difference was observed (P< 0.05). 52% literate and 68% illiterate had low and 48% illiterate and 32% illiterate had moderate/ severe anxiety. 66% married and 45% unmarried and 34% married and 55% unmarried had low and moderate/ severe anxiety respectively. 65% employed and 62% unemployed had low, 35% employed and 38% unemployed had moderate/ severe anxiety. 80% smokers had low and 20% had moderate/ severe anxiety respectively. 61% alcoholics had low and 39% had moderate/ severe anxiety respectively. >5 years of treatment was seen in 47% having low and 53% had moderate/ severe anxiety respectively. A significant difference was observed (P< 0.05). A significant difference was observed in education, smoking and duration of treatment in patients of COPD having depression (P< 0.05). Conclusion: Most of the COPD patients had moderate anxiety and depression.
Keywords: Anxiety; COPD; Depression